A novel role for the cholinergic basal forebrain nucleus of Meynert in chronic pain via modulation of the prelimbic cortex - Oswald, Manfred; Han, Yechao; Kuner, Rohini (Universität, 2022)
This dataset contains all raw electrophysiology data and associated analysis procedures reported in Oswald et al. Cholinergic basal forebrain nucle...